Nettl's elephant : on the history of ethnomusicology - Nettl, Bruno, 1930-2020 (University of Illinois Press, 2010)
Surveying the field he helped establish, Bruno Nettl investigates how concepts such as evolution, geography, and history serve as catalysts for advancing ethnomusicological methods and perspectives. Nettl moves from reflections on the history of ethnomusicology to evaluations of the principal organizations in the field, interspersing those broader discussions with shorter essays focusing on neglected literature and personal experiences. --from publisher description.